New Insights in the Research of Bioactive Compounds from Plant Origin with Nutraceutical and Pharmaceutical Potential - Dincheva, Ivayla; Badjakov, Ilian; Galunska, Bistra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plant bioactive compounds are essential for human health due to their multiple biological effects, such as antioxidant, anticarcinogenic, antiallergenic, anti-inflammatory, antimutagenic, and antimicrobial activities leading to beneficial effects on various non-communicable diseases, such as autoimmune, inflammatory, cardiovascular, cancer, metabolic, and neurodegenerative diseases. Identifying these components, as well as establishing their beneficial health effects, will contribute to the discovery of therapeutics for the prevention and treatment of various disorders. Additionally, the screening of natural sources for novel biologically active metabolites is an essential part of several drug discovery programs.This Special Issue aims to present recent developments in high-throughput and efficient analytical approaches enabling the identification of plant-based compounds, the establishment of new protocols for the evaluation of bioactivities, and methods for the extraction, isolation, and structural characterization of new bioactive components with nutraceutical and therapeutic potential.